PENERAPAN MODEL PEMBELAJARAN KOLABORATIF TIPE GROUP INVESTIGATION DALAM MENUMBUHKAN PERILAKU JUJUR DAN TANGGUNG JAWAB - Kumalasari, Sinar (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The problem in this study originates from the low level of honesty and responsibility among students in Islamic Religious Education (PAI), particularly in the topic "Commendable Behavior is My Identity." Students tended to be passive, hesitant to express their opinions, and often neglected their responsibilities in group tasks. This study aims to describe the implementation of the collaborative learning model, Group Investigation (GI), in fostering honesty and responsibility among third-grade elementary students. This research employed a descriptive qualitative approach and was conducted over three sessions involving 28 third-grade students at SDN 005 Rantau Pulung. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The results indicate that the GI model gradually increased students' active participation, encouraged honest expression of opinions, and fostered a sense of responsibility in group roles. Students demonstrated enthusiasm during discussions, task distribution, and group presentations. Local cultural values were also integrated to strengthen the internalization of character. Through its collaborative and participatory approach, the GI model proved effective in cultivating students' honesty and responsibility.